A case of peripartum cardiomyopathy in primary care - Burkay Yakar; Yusuf Haydar Ertekin; Yasemin Korkut (SERNEV, 2017)
Introduction: Peripartum cardiomyopathy (PKM) is a form of congestive heart failure that results from an enlarging of the heart and a weakening of the heart muscle in the last month of pregnancy and in the first five months of the postnatal period. Major risk factors include pregnancy at gt;30 years of age, multiparity, chronic hypertension and eclampsia. Patients suffering from PKM generally present with symptoms akin to heart failure, and the condition can be considered normal during the late period of pregnancy. A diagnosis of PKM can be made from anamnesis, a physical examination and echocardiography.Case Presentation: A 34-year old female patient, visiting the family medicine polyclinic for vaccinations of her 1-month-old infant, was noted to be suffering from shortness of breath, palpitations and coughing. There was no medical history of any disease or medication before or during the pregnancy. The patient's blood pressure was 120/70 mmHg and her pulse was rhythmic at 122/min. There was no cardiac murmur, rales were present in both pulmonary bases and the results of an abdominal examination were normal. Pitting edemas were observed in both lower extremities, and a further anamnesis revealed that the patient's palpitations had begun two weeks prior to the birth, and had increased in the first postpartum week. The patient was transferred to a cardiologist due to concerns of heart failure and a pulmonary embolism, and was then admitted to the intensive care unit for treatment with a diagnosis of acute decompensated heart failure.Conclusion: Given the higher incidence of disease in mothers gt;30 years, and the advanced average age of maternity in the present day, the odds of encountering PKM in the primary care is increasing. Family physicians can overcome this low-prevalence of the disease by investigating risk factors, following-up symptoms and consulting experts.